Stomatal Characteristics of 5 Citrus L. Species (Rutaceae) From Pekanbaru, Riau Province - Nery Sofiyanti; Putri Intan Wahyuni; Dyah Iriani (Jurnal Biologi Tropis, 2022)
Stomata of leaf is one of the important trait in plant taxonomic study. This trait can be used to characterisize the members of a plant group including Citrus.This genus is one of fruit plant that commonly known in Pekanbaru, Riau. The aim of this study was to examine the characteristic of stomata of 5 Citrus species from Pekanbaru, Riau Province, Indonesia. Leaves were collected from the field. The stomatal preparations were conducted using replica method. Stomata were then observed and photographed using Mikroskop Binokuler Olympus CX23 and Mikroskop LCD Digital Celestron Model 44340. The results show that stomata of all Citrus species examined in this study shows the similar type, hypostomatic with reniform-shaped stomata. However, the variations are found in stomata density and index, as well as the length and length of stomata. C. hystrix and C. aurantifolia have the lowest (419.89/1 mmÃÂ²).), and the highest stomatal density (685.89/1 mmÃÂ²).), respectively. The size of stomata varies within the species. C. microcarpa has the biggest stomata size (20.5 x 18.5 ÃÂµm). ÃÂ Stomatal density of Citrus examined in this study are high (> 500 / mm2) in C. aurantifolia and C. limon) and medium (300 - 500 / mm2) in C. amblicarpa, C. hystrix and C. microcarpa. The density, index and size of stomata can be used to characterize each Citrus members that examined in this study.